Analysis of organic acids in electron beam irradiated chestnuts (Castanea sativa Mill.): effects of radiation dose and storage time - Carocho, Márcio (2013)
Since 2010, methyl bromide, a widely used fumigant was banned from the European Union under the Montreal Protocol guidelines, due to its deleterious effects on health and risk to the environment. Since then, many alternatives for chestnut conservation have been studied (hot water dip treatment being the most common), among them, electron beam irradiation has been proposed as being a safe, clean and cheap alternative. Herein, the effects of this radiation at different doses up to 6 kGy and over storage up to 60 days in the amounts and profile of nutritionally important organic acids were evaluated. Chestnuts contained important organic acids with quinic and citric acids as main compounds. Storage time, which is traditionally well accepted by consumers, caused a slight decrease on quinic (13 to 9 mg/g), ascorbic (1.2 to 0.8 mg/g), malic (5 to 4 mg/g), fumaric (0.4 to 0.3 mg/g) and total organic (33 to 26 mg/g) acids content. Otherwise, irradiation dose did not cause appreciable changes, either individually or in total (28 to 27 mg/g) organic acid contents. Electron beam irradiation might constitute a valuable alternative for chestnut conservation.